Knowledge Aspiring Entrepreneur dan Digitalisasi Pemasaran bagi Pendidik di Lingkungan SMK - Andri Veno; Bella Febrianti; Fatin Fadila; Yuliana Subastine (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study evaluates the effectiveness of a digital marketing workshop for educators at SMKN 1 Kaliwungu in improving participants' knowledge, skills, and satisfaction. The workshop employed a participatory approach, combining instruction, discussion, and practical exercises related to the use of digital media for marketing school products. The research subjects consisted of 24 educators, with data collected through pre- and post-tests. Descriptive analysis showed a significant increase in all indicators, particularly the use of social media, the creation of promotional content, and the selection of digital platforms. The average pretest score of 56.3 increased to 4.2 on a 1–5 Likert scale. Participants reported being very satisfied with the materials and presenters, affirming the effectiveness of the Knowledge Aspiring Entrepreneur (KAE) approach in strengthening teachers' digital literacy. These findings indicate that the digital marketing workshop for educators at SMKN 1 Kaliwungu has proven effective in enhancing participants' knowledge, skills, and satisfaction regarding the concepts and practices of digital marketing. Following the workshop, there was a significant improvement across all indicators, particularly in the use of social media for promoting school products. The participatory training approach—which combined instruction, discussion, and hands-on exercises—was effective in improving teachers' digital literacy and skills. Participants expressed high satisfaction with the materials and presenters, confirming that the Knowledge Aspiring Entrepreneur (KAE) strategy effectively helps educators adopt digital marketing with confidence. It is hoped that this capacity-building initiative can be implemented sustainably to promote the school's creative products while enriching entrepreneurship teaching materials for students.